PERANCANGAN UI/UX APLIKASI PEMESANAN TIKET BIRD PARK PALEMBANG BERBASIS WEBSITE - Cindy Patricia Kadir; Michelle Patricia Wijaya; Monalisa Effendy; Ahmad Farisi; Nora Hafildah (Jurnal Riset Teknik Komputer, 2026)
This study aims to design the user interface and user experience (UI/UX) of a web-based ticket booking system for Bird Park Palembang. Currently, the ticket purchasing process is still conducted manually at the ticket counter, which results in long queues, limited access to information, and inefficient services, particularly during weekends and public holidays. In addition, Bird Park does not yet have an official website that provides centralized information regarding ticket prices and operating hours.This research employs a qualitative approach using the Design Thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. Data were collected through direct interviews with Bird Park employees and visitors, field observations of the ticket purchasing process, and documentation of the promotional media used. The empathize stage was carried out to identify user problems and needs, which were then formulated in the define stage. Design solutions were developed during the ideate stage and implemented in the form of a UI/UX website prototype. Furthermore, the test stage involved users to evaluate ease of use, clarity of information, and interface comfort.The results indicate that the proposed UI/UX design is able to improve the efficiency of the ticket booking process and provide a better user experience compared to the manual system. Therefore, the application of the Design Thinking method is effective in producing a UI/UX design that meets user needs and supports improvements in service quality at Bird Park Palembang.